Implementation of the Pancasila Learner Profile Strengthening Project in Elementary Schools: Implementasi Projek Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Ghefira Azka Ainun Nisa; Abdulah; Refril Dani (Academia Open, 2025)
General Background: Indonesia’s transition to the Merdeka Curriculum aims to address declining educational quality, as reflected in PISA 2019 scores and post-pandemic learning losses. Specific Background: One hallmark of this curriculum is the Pancasila Student Profile Strengthening Project (P5), which promotes cross-disciplinary learning to foster character and 21st-century skills. Knowledge Gap: Prior research has centered on policy-level analysis, with limited empirical studies exploring real implementation of P5 in rural elementary schools, especially regarding internal barriers and school-specific dynamics. Aim: This study examines the implementation, obstacles, and outcomes of P5 at SDN 183/II Sumber Mulya using a mixed-methods approach involving 7 teachers and 15 students. Results: Teacher participation scored 83.29%, while student participation reached 73.59%, indicating a gap in readiness and understanding. Major barriers include limited digital literacy, inadequate training, and teacher workload. Nonetheless, the project yielded tangible products, character development, and improved skills. Novelty: The study highlights localized, contextual analysis of P5 in a rural setting through triangulated qualitative and quantitative data—an approach rarely used in similar studies. Implications: Findings emphasize the need for targeted support, such as community-based learning strategies and local resource utilization, to ensure inclusive and sustainable P5 implementation aligned with national character-building goals.Highlight : Implementation Gap: Teachers show higher readiness and understanding (83.29%) than students (73.59%) in P5 execution. Key Obstacles: Major issues include limited digital skills, lack of training, and high teacher workload. Practical Outcomes: P5 results in character growth, tangible products, and enhanced student skills. Keywords : P5 Implementation, Teacher Obstacles, Student Participation, Project Outcomes, Elementary Context